Focus on the Lymphatic Route to Optimize Drug Delivery in Cardiovascular Medicine - Nolwenn Tessier; Fatma Moawad; Nada Amri; Davide Brambilla; Catherine Martel (MDPI AG, 2021)
While oral agents have been the gold standard for cardiovascular disease therapy, the new generation of treatments is switching to other administration options that offer reduced dosing frequency and more efficacy. The lymphatic network is a unidirectional and low-pressure vascular system that is responsible for the absorption of interstitial fluids, molecules, and cells from the peripheral tissue, including the skin and the intestines. Targeting the lymphatic route for drug delivery employing traditional or new technologies and drug formulations is exponentially gaining attention in the quest to avoid the hepatic first-pass effect. The present review will give an overview of the current knowledge on the involvement of the lymphatic vessels in drug delivery in the context of cardiovascular disease.